2019
DOI: 10.1038/s41598-018-37733-x
|View full text |Cite
|
Sign up to set email alerts
|

Merging Orthovoltage X-Ray Minibeams spare the proximal tissues while producing a solid beam at the target

Abstract: Conventional radiation therapy of brain tumors often produces cognitive deficits, particularly in children. We investigated the potential efficacy of merging Orthovoltage X-ray Minibeams (OXM). It segments the beam into an array of parallel, thin (~0.3 mm), planar beams, called minibeams, which are known from synchrotron x-ray experiments to spare tissues. Furthermore, the slight divergence of the OXM array make the individual minibeams gradually broaden, thus merging with their neighbors at a given tissue dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
9
2
Order By: Relevance
“…Even if MV photons are more abundant in cancer therapy, kV photons come again into play with microbeams or minibeams [210]. kV machines are less expensive, require less shielding, and could make NP-induced cancer radiotherapy available to most countries.…”
Section: Discussionmentioning
confidence: 99%
“…Even if MV photons are more abundant in cancer therapy, kV photons come again into play with microbeams or minibeams [210]. kV machines are less expensive, require less shielding, and could make NP-induced cancer radiotherapy available to most countries.…”
Section: Discussionmentioning
confidence: 99%
“…( d ): Monte Carlo simulations comparing unidirectional depth-dose distributions of 6 MV and 320 kVp X-rays with 320 kVp convergent minibeams. Figures ( a ) and ( b ) are from reference 7 and ( d ) is from reference 33 . Although the 320 kVp energy spectrum is different from the 100 kVp used here (more appropriate for mice), this figure is only intended to present a concept adjusted to human use.…”
Section: Discussionmentioning
confidence: 99%
“…For both mini- and microbeams it was found that blood vessels in the intervening unirradiated segments could repair the irradiated adjacent segments with no consequential residual damage, thus greatly reducing the entrance dose damage 55 . Also, by merging the segmented beams at the tumor, resulting in a damaging broad beam, deep tumors can be selectively irradiated, thus making even unidirectional orthovoltage irradiation superior to megavoltage 33 , 56 (Fig. 6 d).…”
Section: Discussionmentioning
confidence: 99%
“…Even ultrahigh-dose millimeter- and micrometer-wide orthovoltage X-ray beams have surprising yielded minimal normal-tissue damage: intervening minimally irradiated tissues enable almost full repair of many kinds of normal tissues 67 69 . The beams can be interlaced or converged at the tumor, providing an even better dose distribution than with MV X-rays 70 . This technique is now being considered for improving synchrotron and proton radiotherapy 71 73 .…”
Section: Discussionmentioning
confidence: 99%